Repair of Abdominal Aortic Aneurysm in Heart Transplant Patients: Before or after Left Ventricular Assist Device Implantation? - Mehta, G. S. (2011)
Endovascular abdominal aortic aneurysm repair in decompensated heart failure patients requiring ventricular assist device (VAD) placement needs careful consideration of both complex disease states. We present this clinical dilemma and describe our choice of transcatheter aneurysm repair in the face of advanced refractory heart failure following VAD implantation.